EXPLORING EFL TEACHERS' PERSPECTIVES ON CONTINUING PROFESSIONAL DEVELOPMENT OF THE PRIVATE EDUCATION SECTOR IN CAMBODIA - Sovannara Si (Jurnal As-Salam, 2023)
This thesis explored the changing perspectives of EFL teachers on continuing professional development (CPD) in the private education sector in Cambodia. As for professional development, Cambodian education is plagued by a lack of well-trained teachers due to insufficient pedagogical instruction within CPD as well as a lack of commitment by teachers. This study applied quantitative research; data were collected by means of the purposive sampling method with descriptive statistical analysis. Fifty Cambodian EFL teachers teaching three private schools in Kandal province were selected. The findings indicated that EFL teachers acknowledged that CPD is crucial and effective to their professional teaching career when they are more engaged in CPD efficiently. The change in perspectives for Cambodian EFL teachers on CPD has been satisfactorily proven to be fruitful and achievable. Future studies could explore more factors influencing EFL teachers' motivation for Continuing Professional Development activities.